Nonlinear control solutions to prevent slugging flow in offshore oil production. (June 2017) - Jahanshahi, Esmaeil; Skogestad, Sigurd
Abstract : Highlights: The static nonlinearity of the process is mainly due to the valve nonlinearity. Gain-scheduling control of subsea pressure is a robust anti-slug solution. Stabilizability of topside pressure is recovered by applying a nonlinear high-gain observer. The nonlinear high-gain observer diverges when using the subsea pressure measurement. The system with subsea pressure output does not hold the differential observability. Abstract: Feedback control is an efficient and economical solution to prevent slugging flow regimes in offshore oil production. For this, a choke valve at the topside platform is used as the manipulated variable to control the pressure or the flow rate in the pipeline. The primary challenge for anti-slug controllers is robustness. The lack of robustness is due to changes in inflow conditions, the process nonlinearity, and modeling errors. In particular, the nonlinearity combined with an inverse response behavior makes the control of the topside pressure more difficult. We have conducted nonlinear and linear analysis and evaluated four control designs experimentally with both subsea and topside pressures. The control designs are (1) feedback linearization with measured outputs, (2) gain-scheduling IMC (internal model control) based on identified model, (3) PI control with an adaptive gain based on a static gain model, and (4) state feedback with state estimation by a nonlinear high-gain observer. We compared the robustness of these controllers regarding tolerance to time delay, change of the operating point and inflow disturbances. All the controllers could handle 30% step changes (disturbances) in inflow rates and remained stable. The gain-scheduling controller was more robust against time delay than the other controllers. By applying the high-gain observer, the stabilization was achieved in an acceptable range when only the topside pressure was available. However, the observer diverges when using a subsea pressure measurement which from a controllability point of view should be the easiest controlled variable. Nevertheless, this result agrees with the observability theory.